The Impact of Socioeconomic Factors on the HIV-Related Stigma of People Living With HIV in Turkey - Hülya Özkan Özdemir MD; Fatma Nur Karaman Kabadurmuş Ph.D.; Durmuş Özdemir Ph.D (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
This study includes clinical cohort data on 202 People Living with HIV/AIDS (PLWHA) in Izmir, Turkey. Study is conducted at the Izmir Bozyaka Education and Training Hospital, Department of Infectious Diseases and Clinical Microbiology and analyzes the impact of demographic, socio-economic, and clinical factors of HIV stigma, which includes three dimensions of stigma: internalized, anticipated, and enacted. This paper uses clinic data recorded by patients and healthcare professionals of the outpatient clinic. In order to obtain socio-economic measures, patients were interviewed face-to-face. We employ a logistics regression model that aligns with our binary stigma variables. Robustness checks include Ordinary Least Squares and Ordered Logistics models. Our results show that age and marital status are the 2 important demographic factors that affect stigmatized attitudes. Divorced PLWHA have a higher degree of both internalized and anticipated stigma. We find that educated people have a lower degree of internalized stigma. In addition, a higher-income level is found to be inversely associated with enacted stigma. Our results also reveal that LGBTs, drug users, and people who have chronic illnesses have experienced higher stigma levels. This paper explores the complex ways socioeconomic factors contribute to stigma in the Turkish context, addressing a significant gap in the literature since the cultural and social dynamics of stigma in Turkey are frequently overlooked. Recognizing the protective influence of education and income, policies such as integrating HIV education into school curricula and offering financial assistance to PLWHA, especially those from low-income backgrounds, can help reduce stigma.